Do private equity owners increase risk of financial distress and bankruptcy? - Tereza Tykvová; Mariela Borell (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
There is some controversy on the key sources of success in the private equity model and on how this business model affects the portfolio companies. We investigate financial distress risks of European companies around the buyout event in the period between 2000 and 2008. In addition, we analyze whether buyout companies go bankrupt more often than comparable non-buyout companies. Our paper suggests that private equity investors select companies which are less financially distressed than comparable companies and that the distress risk increases after the buyout. Despite this increase, private equity-backed companies do not suffer from higher bankruptcy rates than non-buyout companies. In fact, when companies are backed by experienced private equity funds, their bankruptcy rates are even lower. Experienced investors seem to be better able to manage distress risks than their inexperienced counterparts.
Keywords: G20; G24; G34; 330; private equity; buyout; financial distress; bankruptcy; Private Equity; Übernahme; Unternehmen; Verschuldungsrestriktion; Zahlungsunfähigkeit; Konkurs; Europa